2011
DOI: 10.1007/s00253-011-3354-8
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic diversity, composition structure, and phylogenetic analysis of microbial communities in leachate sediment ecosystems

Abstract: In order to obtain insight into the prokaryotic diversity and community in leachate sediment, a culture-independent DNA-based molecular phylogenetic approach was performed with archaeal and bacterial 16S rRNA gene clone libraries derived from leachate sediment of an aged landfill. A total of 59 archaeal and 283 bacterial rDNA phylotypes were identified in 425 archaeal and 375 bacterial analyzed clones. All archaeal clones distributed within two archaeal phyla of the Euryarchaeota and Crenarchaeota, and well-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Members of the Firmicutes have been observed to provide an important proportion of the microbial communities in comparable ecosystems. Together with the Bacteroidetes, Spirochaetes, as well as the Proteobacteria, they predominated the resident communities in studies of samples from other landfills or leachatecontaminated environments (Röling et al 2001;Liu et al 2011;Huang et al 2004;Huang et al 2005;Zhang et al 2011a). Members of the phylum Actinobacteria have also been detected in other surveys (Röling et al 2001;Huang et al 2004), but the Actinobacteria were represented by very few sequence counts in the Candeias leachates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Members of the Firmicutes have been observed to provide an important proportion of the microbial communities in comparable ecosystems. Together with the Bacteroidetes, Spirochaetes, as well as the Proteobacteria, they predominated the resident communities in studies of samples from other landfills or leachatecontaminated environments (Röling et al 2001;Liu et al 2011;Huang et al 2004;Huang et al 2005;Zhang et al 2011a). Members of the phylum Actinobacteria have also been detected in other surveys (Röling et al 2001;Huang et al 2004), but the Actinobacteria were represented by very few sequence counts in the Candeias leachates.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, relatively few published studies have characterized the microbial populations of landfill leachate, although this issue demands attention given the previously mentioned environmental and economic concerns. Several studies have focused on related ecosystems, such as leachate-contaminated sites (Röling et al 2001;Liu et al 2011) or leachate-treating bioreactors (Calli et al 2006;Xie et al 2012). The existing surveys of raw leachate communities rely on culture-dependent (Hata et al 2004) and culture-independent techniques, such as denaturant gradient gel electrophoresis (DGGE), cloning, and Sanger sequencing of the microbial 16S rRNA gene (Huang et al 2002(Huang et al , 2003(Huang et al , 2004(Huang et al , 2005Laloui-Carpentier et al 2006;Zhang et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…But even with this necessary caution the detected γ-Proteobacteria can be considered as strikingly dominant in four out of five analysed samples. Furthermore, the found sequences in the biofilm show highest similarity to several sequences from diverse geographical origins and habitats, including a coal degrading community in Australia (JQ309095), as well as leachate sediments [39], coking wastewater [40] and also a biocathode community in China [41] (figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…A current synthesis of the available data suggests that JS1 is a characteristic denizen of subseafloor environments, and is particularly abundant in sediments associated with methane hydrates and hydrocarbon seeps, and on continental margins and shelves (Inagaki et al, 2006;Orcutt et al, 2011;Parkes et al, 2014). Sequences related to JS1 have also been detected in environments such as petroleum reservoirs (Pham et al, 2009;Kobayashi et al, 2012), hypersaline microbial mats (Harris et al, 2013), and landfill leachates (Liu et al, 2011). The phylogenetic relationships between OP9, JS1 and other bacterial phyla have not been fully resolved (McDonald et al, 2012), and to date, no axenic cultures have been reported for either of these lineages, although enrichment cultures containing JS1 have been successfully obtained (Webster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%